Management of English Courses in Virtual Learning During the COVID-19 Pandemic - Yulianingsih, Wiwin; Roesminingsih, M. V.; Mardliyah, Sjafiatul; Lutviatiani, Mita; Rofiah, Khofidotur (Journal of Nonformal Education, 2023)
The existence of the COVID-19 pandemic has succeeded in transforming the implementation of offline learning activities into online. This does not only occur in formal educational institutions, but also in non-formal educational institutions such as the Mahesa Institute Course and Training Institute (LKP) as an English language course institution. The purpose of this study is to examine management as a strategy for LKP Mahesa Institue in maximizing learning methods applied during the COVID-19 pandemic as well as to examine the enthusiasm of learning residents during distance learning. The research method used in this research is qualitative with a descriptive approach. The data analysis technique applied is Miles and Huberman's analysis theory which consists of the stages of reduction, presentation, and drawing conclusions. The results obtained from this study are that in the management process, LKP Mahesa Institute is by improving the skills of educators and learning residents through virtual learning activities so that they can improve the learning outcomes carried out. Novelty from research conducted in the application of the virtual learning model at the LKP Mahesa Institute non-formal education institution is able to increase the learning speed of learning citizens anytime and anywhere, increase collaboration while increasing mastery of learning resources, and being able to create different learning experiences. So, with this research it is hoped that it can become a source of information in developing the management of English courses.